The impact of a canine-assisted reading program on readers needing extra practice - Bernstein, Elana R.; Davies, Susan C.; Justice, Ann F. (New Jersey: Wiley Company, 2023)
This study investigated the impact of incorporating a service dog in programming for students needing extra reading practice. Brief sessions involving reading to a dog improved students' attitudes toward reading.
Keywords: Reading. -- Program. -- Service dof